Integrating Faith and Learning in the Western Civilization Classroom - Pardue, Brad (Christian higher education, 2018)
This essay reflects on the author's efforts to incorporate a distinctly Christian worldview into the design and pedagogy of a two-semester western civilization survey sequence, two courses required of all students as part of a General Education curriculum. While drawing on the extensive and growing secondary literature on the integration of faith and learning, this essay examines more concrete efforts to embed such issues into the syllabi, required readings, assignments, and class discussion of a particular set of courses. The author explores various avenues for engaging students in the difficult but rewarding effort to let Christian truths inform both historical scholarship and a general understanding of the past.